Side-effect monitoring of continuing LAI antipsychotic medication in UK adult mental health services - Carol Paton; Tom K. J. Craig; Brittany McConnell; Thomas R. E. Barnes (SAGE Publishing, 2021)
Background: Long-acting injectable (LAI) antipsychotic medications are used to optimise treatment outcomes in schizophrenia. Guaranteed medication delivery increases the responsibility of prescribers to monitor and manage adverse effects. Methods: In the context of a quality improvement programme conducted by the Prescribing Observatory for Mental Health, a clinical audit addressed documented side-effect monitoring in patients prescribed continuing LAI antipsychotic medication under the care of United Kingdom adult mental health services. Results: A total of 62 mental health services submitted data on 5169 patients prescribed LAI antipsychotic medication for more than a year. An assessment of side effects had been documented in the past year in 2304 (45%) cases. Post hoc analysis showed that extrapyramidal side effects were more likely to have been assessed and found to be present in those patients prescribed LAI haloperidol, flupentixol or zuclopenthixol. There was little other targeting of assessments to the known side effects profiles of individual LAI antipsychotic medications, but when dysphoria had been assessed it was most commonly found with LAI haloperidol treatment and when weight gain, sexual and prolactin-related side effects had been assessed, they were more often identified with LAI paliperidone. Conclusion: The data suggest a relatively low frequency of side-effect assessments, largely untargeted. This is likely to result in many adverse effects going unrecognised and unmanaged, thus failing to tackle their potential to confound mental state assessment and adversely affect physical health and adherence. Patients receiving LAI antipsychotic medication have regular contact with a healthcare professional who administers the medication, which provides an opportunity to potentially remedy this situation.